Natural Resource Management among Small-scale Farmers in Semi-arid Lands: Building on Traditional Knowledge and Agroecology - Altieri, Miguel A; Tolcdo, Victor M (Annals of Arid Zone, 2016)
Although risk and uncertainty dominate the lives of most rural inhabitants of the semi-arid regions of the world, many farmers have been able to develop durable farming systems through the use of innovative soil and water management systems and the use of locally adapted crop species and varieties. In this paper we Plovide examples of farming systems developed by traditional farmers well adapted to the local conditions of the semi-arid environment, enabling farmers to generate sustained yields meeting their subsistence needs, despite harsh conditions and low use of external inputs. Part of this performance is linked to the ingenious soil and water conservation systems but also to the high levels of agrobiodiversity exhibited by traditional agroecosystems, which in turn positively influences agroecosystem function. We also give examples of projectsÂ· aimed at assisting rainfed resource-poor farmers in the development of a variety of practical techniques and strategies to enhance production and resiliency in the midst of resource constraints typical of semi-arid environments. Many of these efforts use elements of modem science but that build upon traditional knowledge by including farmers in the development process.